2014
DOI: 10.1002/rcm.6810
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-assisted laser desorption/ionization time-of-flight mass spectrometric imaging of synthetic polymer sample spots prepared using ionic liquid matrices

Abstract: Ionic liquid matrices can be used to overcome segregation, a typical drawback of conventional MALDI dried-droplet preparations. Homogeneous sample spots are easy to prepare, stable in the MS vacuum and, thereby, improve the reproducibility of MALDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 49 publications
4
28
0
1
Order By: Relevance
“…It has been observed that it is simple to detect hydrophobic biomolecules with hydrophobic matrices since hydrophobic matrices have good affinities for hydrophobic analytes . Therefore, there have been several efforts to synthesize new hydrophobic matrices for analyses of hydrophobic biomolecules . However, synthesis of such matrices often involves complex synthetic procedures, which are time consuming and at the same time often produce low product yields.…”
mentioning
confidence: 99%
“…It has been observed that it is simple to detect hydrophobic biomolecules with hydrophobic matrices since hydrophobic matrices have good affinities for hydrophobic analytes . Therefore, there have been several efforts to synthesize new hydrophobic matrices for analyses of hydrophobic biomolecules . However, synthesis of such matrices often involves complex synthetic procedures, which are time consuming and at the same time often produce low product yields.…”
mentioning
confidence: 99%
“…23 In contrast to solid matrices, such as CHCA and 2,5-DHB, the data also show that the ion intensities are uniform across the sample surface. 49 MALDI-MSI shows a superior sample spot homogeneity using ILMs and no differences in the mass spectra and showed high stability under vacuum and less fragmentation. Using ILMs, fragment ions characteristic of proteins, most likely from the cell nuclei, were observed, which were not observed in SIMS images of control samples (no matrix applied).…”
Section: Mass Spectrometry Imagingmentioning
confidence: 99%
“…The use of organic matrices in MALDI-MS can, however, result in an inhomogeneous distribution of analyte crystals, leading to poor reproducibility [10,11]. In addition, polymers subjected to highpower UV-laser irradiation in MALDI-MS can undergo undesirable fragmentation [12][13][14]. Consequently, the complicated array of fragment ions will result in higher MS background noise and loss of MS resolution, making it more difficult to determine the full chemical structure and molecular weight of the polymer.…”
Section: Introductionmentioning
confidence: 96%